A five-year strategic plan for Davao Doctors College, Inc. (College of Nursing) - Cabrera, Rueben Higino S.; Digal, Larry N.; Concepcion, Sylvia B.; Gomez, Aurelia Luzviminda V. (Davao City School of Management, University of the Philippines Mindanao, 2008)
The last part of the 90?s saw conditions in developed countries, most notably the U.S. and U.K., like an expanding population of baby-boomers, a robust economy, and a change in job preferences of the next generation combine to provide an excellent opportunity for the Filipino nurses to pursue their dreams. The rising numbers of Filipino nurses or any OFW for that matter, migrating to these countries and the success that they have achieved had a tremendous effect on their lives and to the country?s economy as well. This phenomenon was the stimulus for the increased interest from parents, students, and even professionals to consider becoming s registered nurse. In return, colleges and universities responded quickly as the number of schools offering nursing went up and began churning graduates up to a point that there are presently more than 400,000 unemployed nurses. During this period, Davao Doctors College, Inc. flourished with its student population growing from 2500 n 2002 reaching a peak of 5050 in 2005 and concomitant growth in revenues of Php 49M to Php 264M, respectively. However, the performance of the school deteriorated gradually due to a combination of factors namely the increased turnover rate of clinical instructors, low entrance standards, and low patient to student ratio. In 2008, the number of new enrollees in the College of Nursing has fallen drastically and with the change in the ownership structure of the firm, DDC needed a new strategy to survive in an increasingly competitive and difficult environment. An adaptation of the strategy planning process by Fred David is the basis for this strategic plan. Data for the external environment are secondary data from various articles from newspaper, magazines, and website while data for the internal environment are primary data from interviews with the members of the Executive Council and other school staff, school records, and presentations during the DDC Visioning and Strategic Planning Workshop. An analysis of the external environment reveals the firm?s opportunities and threats and the likely scenario is that there will be an intense competition for market share in a shrinking market due to the domestic oversupply situation and depressed demand due to the global financial crisis. According to the External Factor Evaluation Matrix, DDC as an organization is in a position to weather this through. However, it must turn its attention to using its strengths to gain advantage and addressing its weaknesses in order to survive as its Internal Factor Evaluation Matrix shows that it is internally weak. By incorporating the identified external opportunities and threats, and the internal strengths and weaknesses into a SWOT Matrix, we were able to formulate the strategic options. With the use of the Quantitative Strategic Planning Matrix, the strategic choice is Product Development. Product development aims to make the nursing program and the firm itself more attractive than its competitors or rivals in the eyes of its customers. The strategy is to address a major weakness of the school, which is the chronic turnover of clinical instructors and having replacements that are not properly equipped or ready to be clinical instructors, through a recruitment and scholarship program. This program should lessen the turnover rate to manageable levels by making the turnover predictable through a return service agreement or contract between the school and the clinical instructor. In addition, the program decreases the exposure of the firm to bad investments in cases of breach of contract. It is worthwhile to mention that the scholarship program should elevate the quality of instruction being given by the school and should translate to globally competitive graduates.
Thesis, Graduate (Master in Management)--University of the Philippines MIndanao, December 2008.
Keywords: Strategic plan